Prohibitin overexpression predicts poor prognosis and promotes cell proliferation and invasion through ERK pathway activation in gallbladder cancer. Issue 1 (December 2016) - Cao, Yang; Liang, Haibin; Zhang, Fei; Luan, Zhou; Zhao, Shuai; Wang, Xu-an; Liu, Shibo; Bao, Runfa; Shu, Yijun; Ma, Qiang; Zhu, Jian; Liu, Yingbin
Abstract Background Prohibitin (PHB), a pleiotropic protein overexpressed in several tumor types, has been implicated in the regulation of cell proliferation, invasive migration and survival. However, PHB expression and its biological function in gallbladder cancer (GBC) remain largely unknown. Methods PHB and p-ERK protein expressions were determined in human GBC tissues by immunohistochemistry (IHC). The effects of PHB knockdown on GBC cell proliferation and invasiveness were evaluated using Cell Counting Kit-8 (CCK-8) cell viability, cell cycle analysis, transwell invasion and gelatin zymography assays. Subcutaneous xenograft and tail vein-lung metastasis tumor models in nude mice were employed to further substantiate the role of PHB in GBC progression. Results PHB protein was overexpressed in GBC tissues and was significantly associated with histological grade, tumor stage and perineural invasion. Furthermore, PHB expression was negatively associated with overall survival in GBC patients. In vitro experimental studies demonstrated that the downregulation of PHB expression by lentivirus-mediated shRNA interference not only inhibited the ERK pathway activation but also reduced the proliferative and invasive capacities of GBC cells. Moreover, PD0325901, a specific inhibitor of MEK, markedly impaired PHB- mediated phosphorylation of ERK protein. IHC statistical analyses further validated that PHB expression was positively correlated with ERK protein phosphorylation levels in GBC tissue samples. In vivo, PHB depletion also resulted in dramatic reductions in the growth and metastasis of GBC cells. Conclusion Our findings demonstrate that PHB overexpression predicts poor survival in GBC patients. PHB could serve as a novel prognostic biomarker and a potential therapeutic target for GBCs.